2013
DOI: 10.1177/1934578x1300801234
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Antiproliferative and Antimicrobial Activities of the Volatile Oil from the Wild Pepper Piper capense Used in Cameroon as a Culinary Spice

Abstract: Wild pepper (Piper capense L.f., Piperaceae) is a spice traditionally used in western Cameroon to make soups called 'Nkui' and 'Nah poh'. In the present work, the essential oil hydrodistilled from fruits was analyzed by GC-FID and GC-MS, and for in vitro biological activities, namely cytotoxic, antioxidant and antimicrobial, by MTT, DPPH, ABTS and agar disc diffusion methods. The oil composition was dominated by monoterpene hydrocarbons (56.5%) responsible for the pepper odor, such as β-pinene (33.2%), sabinen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
2
15
0
1
Order By: Relevance
“…The chemical composition of the essential oil of P. capense seed was comparable to those reported in the literature (Woguem et al, 2013, Amvam Zollo et al, 1998, Tchounbougnang et al, 2009). Indeed, previous study showed that essential oil obtained from P. capense seed is mainly constituted by monoterpenes (64.7%) with predominance of hydrocarbons (56.5%).…”
Section: Differences In the Extraction Yields Were Noted Betweensupporting
confidence: 86%
See 2 more Smart Citations
“…The chemical composition of the essential oil of P. capense seed was comparable to those reported in the literature (Woguem et al, 2013, Amvam Zollo et al, 1998, Tchounbougnang et al, 2009). Indeed, previous study showed that essential oil obtained from P. capense seed is mainly constituted by monoterpenes (64.7%) with predominance of hydrocarbons (56.5%).…”
Section: Differences In the Extraction Yields Were Noted Betweensupporting
confidence: 86%
“…Indeed, previous study showed that essential oil obtained from P. capense seed is mainly constituted by monoterpenes (64.7%) with predominance of hydrocarbons (56.5%). Major constituents were monoterpene hydrocarbons: α-pinene (8.9%), sabinene (10.0%), β-pinene (33.2%) and sesquiterpene hydrocarbons: α-caryophyllène (6.3%) and germacrene D (3.8%) (Woguem et al, 2013). Other studies also reported that major volatile compounds of fruits from Western Cameroon were monoterpene hydrocarbons: α-pinene (10.5-14.4%), sabinene (14.7-17.4%), β-pinene (46.8-59.3%) and sesquiterpene hydrocarbons:…”
Section: Differences In the Extraction Yields Were Noted Betweenmentioning
confidence: 99%
See 1 more Smart Citation
“…These oils are basically composed of phenylpropanoids, such as safrole, dillapiole and myristicin, and/or terpenes, such as limonene, β-caryophyllene, spathulenol, (E)-nerolidol, bicyclogermacrene and α-cadinol (Guerrini et al 2009;Santos et al 2001;Maia and Andrade 2009). Investigations of the biological properties of essential oils from this genus have revealed antimicrobial (Oliveira et al 2016), antioxidant (Woguem et al 2013), acaricidal (Araújo et al 2012) and insecticidal activities (Santana et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, complexity of the reaction system and high cost of the catalyst prevented the scale-up of the synthetic route at industrial levels [4]. Currently, sabinene is mainly isolated from plants which greatly limits the large-scale production and application of these compounds due to its low content in plant materials [10].…”
mentioning
confidence: 99%